2022
DOI: 10.22551/2022.35.0902.10204
|View full text |Cite
|
Sign up to set email alerts
|

Wandering spleen with torsion: a rare cause of acute abdomen in a 14-year-old girl

Abstract: Wandering spleen is a rare condition and defined as the spleen that is not in its normal anatomical position due to lack or laxity of suspensory ligaments. Etiological factors are congenital and acquired. Splenic torsion, infraction, and rupture are life-threatening complications of wandering spleen. A 14-year-old girl patient presented to the emergency department with severe pain abdomen for 2 days. On physical examination, a large palpable mass in the mid of the abdomen was found, and CECT confirmed it as to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…In addition, many cases of wandering spleen with torsion are reported as a rare cause of acute or recurrent abdominal abdomen pain, even without infarction. [14][15][16][17] Our report also showed that real-time ultrasound is useful to identify symptomatic ectopic intramesenteric AS, revealing the precise topographic correspondence with the site of pain. Exact correspondence between the pain felt by the patient and the small nodule detected by ultrasound, as well as the pain evoked by the gentle compression with the sonographic probe just above the lesion, may be useful in the differential diagnosis.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In addition, many cases of wandering spleen with torsion are reported as a rare cause of acute or recurrent abdominal abdomen pain, even without infarction. [14][15][16][17] Our report also showed that real-time ultrasound is useful to identify symptomatic ectopic intramesenteric AS, revealing the precise topographic correspondence with the site of pain. Exact correspondence between the pain felt by the patient and the small nodule detected by ultrasound, as well as the pain evoked by the gentle compression with the sonographic probe just above the lesion, may be useful in the differential diagnosis.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, many cases of wandering spleen with torsion are reported as a rare cause of acute or recurrent abdominal abdomen pain, even without infarction. 14 17…”
Section: Discussionmentioning
confidence: 99%
“…Wandering spleen (or ectopic spleen) refers to a hyper-mobile spleen resulting in its displacement from normal anatomical position in the left hypochondrium to an ectopic site usually in the lower abdominal or the pelvic cavity [ 1 , 2 ]. Considered a rare clinical presentation with an overall incidence rate of less than 0.2%, it has been reported mostly in children within the first decade of life.…”
Section: Discussionmentioning
confidence: 99%
“…A laparoscopic splenopexy is the most practiced approach where splenic preservation is necessary (usually under 30 years of age) [ 14 ]. Splenectomy is a preferable choice in conditions of splenic infarction, hypersplenism, or splenomegaly [ 2 , 15 ]. Our patient presented with pedicle torsion and splenic infarction hence, a splenectomy was performed.…”
Section: Discussionmentioning
confidence: 99%